Ecological Hermeneutics: The Story of Humanity and the Garden of Eden as a Depiction of Relational Ecological Creation Theology (Genesis 2: 8-17) - purba, Sinear; Simarmata, Amsal (Sekolah Tinggi Teologi Trinity Parapat, 2024)
Nature is part of human life. But, the humans as imago Dei often abuse their superiority over other creations. The Bible tells that God formed humans from the Earth in His image and likeness, then breathed into them (Gen. 2:7). Glory, honor, and power to subdue the earth and all other creations are given to humans (Gen. 1:26-28; 5:1; 9:6). Humans understand this as justification for acts of control and destructive-exploitative treatment of nature and all creations and to fulfill human interests. So Theology as part of human reflection on this reality needs to respond to do something about this phenomenon. Through the Story of the Garden of Eden in Genesis 2: 8-17, it is the story of the beginning of harmonious creation according to God's will which is described as something good. This becomes a discussion starter about how the ideal picture of the relationship of each creation with an ecological hermeneutic approach finds and shows the complexity of the relationship between God, Man and other creations. This story becomes a picture of relational theology as an effort to bring each other to life as fellow creations on this earth.